Underdevelopment of gut microbiota in failure to thrive infants of up to 12 months of age - Zhang, Mei; Miao, Dan; Ma, Qi; Chen, Tao; Wang, Tuanmei; Yan, Shuyuan; Zhu, Wendan; Zhou, Fan; He, Jun; Kuang, Xiaoni (Frontiers in Cellular and Infection Microbiology, 2022)
Laboratory and clinical studies have revealed the importance of gut microbiota in children with severe pediatric pathological conditions such as severe acute malnutrition (SAM); however, under relatively milder conditions such as, failure to thrive (FTT), the role of the gut microbiota remains poorly characterized. Here, we analyzed stool samples from 54 subjects with a clinical diagnosis of failure to thrive (FTT), 49 preterm subjects with corrected normal growth (NFTT-pre), and 49 healthy subjects (NFTT) between 3-12 months of age using 16S rRNA gene sequencing. We observed that the clinical condition of FTT, age, head circumference, intrauterine growth restriction (IUGR), and feeding methods significantly affected gut microbiota. The microbiota age of subjects was significantly correlated with their anthropomorphic features, and the FTT subjects exhibited underdeveloped gut microbiota characterized by a significantly decreased microbiota-for-age Z-score (MAZ). The FTT and NFTT-pre groups exhibited an obvious disrupted developmental trajectory of gut microbiota across age, and the development of their alpha diversities and the observed OTU and Shannon indices were inadequate, particularly in subjects with FTT. Moreover, sequential colonization and enrichment of bacteria such as Bacteroides, Bifidobacterium, Streptococcus and most age-discriminatory bacterial taxa and their microbial functions were disorganized in FTT compared to that in NFTT. Our results revealed an underdevelopment of the gut microbiota in infants with failure to thrive that possesses potential clinical and practical importance.